Processo terapêutico da criança em transplante de medula óssea: práticas de terapeutas ocupacionais do Estado de São Paulo - Idemori, Thais Clemente (2015)
Childhood cancer was encompassed as a priority in the public health agenda in Brazil. One of the procedures commonly used is the Bone Marrow Transplantation. The procedures are of high complexity and represent a series of restrictions to patients. A child illness and hospitalization can foster changes in daily life activities, play, leisure, school activities and social participation that will interfere with his/her development and occupational activities. Occupational Therapy procedures seek to provide a more accessible experience in hospital concerning the possibilities of involvement, favoring his/her development through activities. The objective of this study was to describe actions in the occupational therapy responsible for promoting the participation and autonomy in school age children who have undergone bone marrow transplantation, from the perception of occupational therapists. The research was conducted with the report of six practitioners addressing their experience and observations with children who have undergone the transplant. This is a descriptive study with a qualitative approach. A short form of personal and professional identification and characterization and a semi-structured interview script were used as data collection instruments. Aiming adequacy of the interview script, it was submitted to a pilot study in order to perform any needed adjustments. After the data collection, the interview was transcribed verbatim and analyzed under the Content Analysis overview. Through the content obtained in the interviews it was possible to draw themes that were gathered giving rise to four categories: (1) contexts and occupational roles affected by illness, hospitalization; (2) Occupational Therapy processes; (3) benefits to children by occupational therapy activities and the actions developed by occupational therapists; (4) successful practices; essential factors and theoretical principles. The results showed that even though there are variations, the occupational therapist s main practice purpose is to minimize the effects children may experience by the illness and hospitalization. The reapproach to autonomy and the stimulation for the children to get involved in activities were obtained by different therapeutic processes and is related to the formation of the therapist, the child's age and level of development and the use of specific techniques anchored in theoretical bases related to his/her education. This is due to the fact that there are therapists who focus on the organic nature of changes related to the child s needs, while others focus on his/her psychosocial changes. Most therapists use a dynamic approach. The promotion of participation and autonomy reported by the professionals were developed in a therapeutic process, in which the cited activities illustrate the use of that instrument. Current strategies of communication (mail, internet and telephone) have been used to favor the child's communication with his/her environment during the hospitalization process. There are therapists who work in a systemic perspective, in which the various systems that the child takes part are considered for intervention in Occupational Therapy and thus the family, the school, the hospital and the actions that involve nonimmediate contexts, gain importance in the child's different occupational roles. Non-normative life events, such as parents divorce along with hospitalization and transplantation magnify the child's fragile condition. There are other situations, however, where the provision of resources by the hospital positively enhanced the child's quality of life. It is expected that the description of the practices in Occupational Therapy reported here, particularly those responsible for stimulating participation and autonomy in activities for children in school age who have experienced the process of bone marrow transplantation and also the identification of daily life contexts that benefit from this promotion, may contribute to knowledge development in Occupational Therapy in the Brazilian environment.